2020
DOI: 10.1002/anie.202010531
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Control of Initial Coulombic Efficiency for Lithium‐rich Manganese‐based Layered Oxides by Surface Multicomponent Integration

Abstract: Low initial Coulombic efficiency (ICE) is an obstacle for practical application of Li-rich Mn-based layered oxides (LLOs), which is closely related with the irreversible oxygen evolution owing to the overoxidized reaction of surface labile oxygen. Here we report a NH 4 F-assisted surface multicomponent integration technology to accurately control the ICE, by which oxygen vacancies, spinel-layered coherent structure, and F-doping are skillfully integrated on the surface of treated LLOs microspheres. Though the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
68
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(71 citation statements)
references
References 42 publications
2
68
0
1
Order By: Relevance
“…[14] Other studies showed that Ti-doped Li(Ni x Mn x Co 1-2x-y Ti y )O 2 not only increased the energy density but also enhanced the structural stability upon cycling because of the elevated Ti-O bond energy. [15] Chen et al reported that when F À occupied the O sites in Li-rich layered oxides, cycling stability was enhanced by 94.8% in 50 cycles between 2.0 and 4.8 V. [16] Small amounts of Fe-doped LiNi 1/3 Co 1/3 Mn 1/3 O 2 prepared by simple sol-gel method also displayed slight volume change in the material during Li þ diffusion, resulting in excellent structural stability. [17] In addition, other elements such as Al, [18,19] Cr, [20] Zr, [21,22] and Zn [23,24] have been also explored.…”
mentioning
confidence: 99%
“…[14] Other studies showed that Ti-doped Li(Ni x Mn x Co 1-2x-y Ti y )O 2 not only increased the energy density but also enhanced the structural stability upon cycling because of the elevated Ti-O bond energy. [15] Chen et al reported that when F À occupied the O sites in Li-rich layered oxides, cycling stability was enhanced by 94.8% in 50 cycles between 2.0 and 4.8 V. [16] Small amounts of Fe-doped LiNi 1/3 Co 1/3 Mn 1/3 O 2 prepared by simple sol-gel method also displayed slight volume change in the material during Li þ diffusion, resulting in excellent structural stability. [17] In addition, other elements such as Al, [18,19] Cr, [20] Zr, [21,22] and Zn [23,24] have been also explored.…”
mentioning
confidence: 99%
“…For example, Zhang et al 9 the electrochemical process, thus promoting ICE. Luo 10 and coworkers reduced the content of unstable oxygen on the surface using F − for surface modification and greatly improved the ICE. Likewise, a lot of reagents were selected to realize pre-activation, such as Na 2 S 2 O 8 , (NH 4 ) 2 SO 4 , and NH 4 H 2 PO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Although these preactivation methods can effectively improve the performance, they also induced the deterioration of cycle stability and the voltage drop during the discharge process and thus reduced the energy density for the LRMO material. 10,16 Specially, Zhu et al 17 reported a molten-assisted way to create LRMO particles with a Li-poor surface and Li-rich core. The continuous Ligradient kept the overall structure stable and greatly improved the electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations